MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN 1 SAMPAI 10 MELALUI METODE VAKT BAGI ANAK TUNAGRAHITA SEDANG - Zulkifli Zulkifli; Fatmawati Fatmawati; Tarmansyah Tarmansyah (Jurnal Penelitian Pendidikan Khusus, 2013)
Children's mental retardation moderate grade IV had difficulty in recognizing numbers. The perceived difficulty of teachers, providing guidance not optimal, media less have variation, while VAKT method has never been used in learning. The purpose of this study the ability of the child to know that numbers 1 to 10 increased. The study was designed using classroom action research methodology. Data obtained through the introduction of number child observation and tests. The results of the cycle I and II that VAKT method can increase the ability of mental retardation moderate in children recognize numbers.